2002
DOI: 10.3201/eid0802.010244
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Antimicrobial Resistance in Taiwan

Abstract: While some trends in antimicrobial resistance rates are universal, others appear to be unique for specific regions. In Taiwan, the strikingly high prevalence of resistance to macrolides and streptogramin in clinical isolates of gram-positive bacteria correlates with the widespread use of these agents in the medical and farming communities, respectively. The relatively low rate of enterococci that are resistant to glycopeptide does not parallel the high use of glycopeptides and extended-spectrum beta-lactams in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 37 publications
7
88
0
2
Order By: Relevance
“…The rate of resistance to clindamycin (92.9%) among the C-MRSA iso- lates from subjects without risk factors in this study was also higher than that in a study from the United States (10), in which most C-MRSA isolates from subjects without risk factors were susceptible to clindamycin. The high rate of resistance to clindamycin among our community MRSA isolates (90.6%) was similar to the rate of resistance among clinical MRSA isolates in Taiwan (94.2%) (13,41), indicating that clindamycin resistance is quite common among community and health care facility-related MRSA isolates in Taiwan. This study found that recent receipt of medical services was the major factor associated with MRSA colonization as well as the high level of multiple-drug resistance in MRSA nasal isolates.…”
Section: Discussionmentioning
confidence: 55%
“…The rate of resistance to clindamycin (92.9%) among the C-MRSA iso- lates from subjects without risk factors in this study was also higher than that in a study from the United States (10), in which most C-MRSA isolates from subjects without risk factors were susceptible to clindamycin. The high rate of resistance to clindamycin among our community MRSA isolates (90.6%) was similar to the rate of resistance among clinical MRSA isolates in Taiwan (94.2%) (13,41), indicating that clindamycin resistance is quite common among community and health care facility-related MRSA isolates in Taiwan. This study found that recent receipt of medical services was the major factor associated with MRSA colonization as well as the high level of multiple-drug resistance in MRSA nasal isolates.…”
Section: Discussionmentioning
confidence: 55%
“…5 Before the 2003 epidemic of severe acute respiratory syndrome, the prevalence of HA-MRSA in Taiwan increased from 26.7% in 1990 to 60% in 1998-2000, 6 then increased to 53-83% in 2003. 7 Interestingly, after the 2003 severe acute respiratory syndrome epidemic, there was a decline in the prevalence of HA-MRSA in Taiwan. Lee et al 2 reported that the prevalence of MRSA decreased from 63.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of pandrug-resistant A. baumannii (PDRAB), which are resistant to all antibiotics routinely tested (i.e., ampicillin-sulbactam, ceftazidime, piperacillin-tazobactam, cefepime, aztreonam, ciprofloxacin, trovafloxacin, moxifloxacin, garenoxacin, amikacin, imipenem, and meropenem), were first recovered in May 1998 at the National Taiwan University Hospital (NTUH) (14,17). Since then, clusters of PDRAB infections and nosocomial outbreaks have persisted, although the incidence of nosocomial infections caused by PDRAB has declined in the past 2 years (12,13,15).…”
mentioning
confidence: 99%